ANALISIS DWELLING TIME IMPOR PADA PELABUHAN TANJUNG PRIOK MELALUI PENERAPAN THEORY OF CONSTRAINTS - Anita, Sherly Luthfi; Asmadewa, Indra (JURNAL PERSPEKTIF BEA DAN CUKAI)
AbstractThe objective of this research is to identify dwelling time bottlenecks in green and yellow channel of importation, the bottleneck causes, and how to solve the contraints. Using theory of constraints, this study conducts five-focusing steps to solve the problems. This qualitative research takes Port of Tanjung Priok as the location to observe and invloves three groups of participant consisting of regulatory institution, port operator, and ten importers as the service users. This study concludes that the main bottleneck of dwelling time can be identified in pre-clearance process that is the lengthy time of processing and issuing importation permission of prohibitted and/or restricted goods. Some causes of the bottleneck are identified covering importers’ lack of knowledge about regulation of prohibitted and/or restricted goods, unintegrated permission process with Indonesia National Single Window, and many different technical institutions involved. The proposed solutions for the constraints faced in the port are single submission and Indonesia Single Risk Management. These solutions are considered to have ability to shorten current dwelling time.     Kata kunci: dwelling time, theory of constraints, bottleneck, Indonesia National Single Window, prohibitted and/or restricted goods AbstrakPenelitian ini bertujuan untuk mengetahui apa yang menjadi penghambat (bottleneck) dalam dwelling time impor jalur kuning dan jalur hijau, mengapa bottleneck terjadi, dan bagaimana mengatasi bottleneck tersebut. Dengan menggunakan theory of constraints, penilitian ini melakukan lima langkah fokus (five-focusing steps) untuk mencari solusi atas kendala yang ditemukan. Penelitian kualitatif ini mengambil tempat di Pelabuhan Tanjung Priok dengan melibatkan tiga pihak yaitu regulator, operator pelabuhan dan sepuluh pengguna jasa. Penilitian ini menyimpulkan bahwa kendala utama yang ditemukan dalam dwelling time adalah pada tahap pre-clearance yaitu lamanya waktu pemrosesan dan penerbitan izin impor barang larangan dan/atau pembatasan. Sejumlah penyebab atas kendala yang dapat diidentifikasi mencakup ketidaktahuan importir tentang ketentuan lartas, proses perizinan yang belum terintegrasi dengan Indonesia National Single Window, dan proses perizinan yang melibatkan banyak instansi teknis. Usulan solusi atas kendala tersebut yaitu single submission dan Indonesia Single Risk Management memiliki kemampuan untuk mengatasi kendala dwelling time saat ini.  Kata kunci: dwelling time, teori kendala, penghambat, Indonesia National Single Window, barang larangan dan/atau pembatasan